The genus Amphorotia (Bacillariophyta) in subtropical Asian coastal areas: Species diversity in fossil material from the Pearl River system, China. Issue 1 (2nd January 2019) - Wu, Cong; Williams, David M.; Flower, Roger J.; Chen, Fang; Zhou, Yang; Chen, Chixin
ABSTRACT: Amphorotia is a diatom genus of considerable morphological and biogeographical significance. It was established by transferring several Eunotia species and describing several new species. The most species were found dispersed towards Southeast Asia. In coastal areas of China, a number of species of Amphorotia were found and the assemblages contained several new taxa. This article provides additional information on five previously described species and describes one new species, Amphorotia zhujiangensis sp. nov., and one uncertain but special species, A . sp. These are based on fossil material from a deltaic borehole, subaquatic sediment cores and surface sediments collected in the Pearl River estuary region. Morphological data were derived from light and scanning electron microscopy. A detailed morphological comparison of seven Amphorotia species is included, indicating the existence of a diverse group in brackish waters. Relationships within the family Eunotiaceae are briefly discussed. The biogeographical range of regional habitats occupied by Amphorotia species in tropical Southeast Asia is also expanded.